Hubungan Mikroklimat terhadap Populasi Sapi Perah Friesian Holstein di BPTSP HPT Cikole Lembang : The Correlation of Microclimate on Population of Friesian Holstein Dairy Cattle at BPTSP HPT Cikole Lembang (Jurnal Agroekoteknologi dan Agribisnis, 2022)
The purpose of this study was to determine the correlation between microclimates in FH dairy cattle at BPTSP HPT Cikole. The main material in this study was data on the population of Friesian Holstein (FH) dairy cattle of 111 heads raised from 2017 to 2019. Additional data used in this study are temperature, humidity, precipitation, and temperature humidity index from January 2017 to December 2019. The data processed into parameters included livestock populations affected by microclimate. Data processing methods used descriptive analysis, regression, and correlation. The total population in ST from 2017 to 2019 was different. In 2018 the population increased from the previous year, but in 2019 the population decreased. Based on regression and correlation analysis, there was a noticeable influence between humidity and precipitation on the FH cattle population with R2 values of 33.36% and R2 of 40.28%. It can be concluded that there was no significance correlation between microclimate and cow physiological condition. Therefore, the microclimates consisting of temperature, humidity, precipitation, and THI gave no effect on the Friesian Holstein cattle physiological conditions.